Understanding the Psychological Motives Behind Microblogging - QIU, Lin (Institutional Knowledge at Singapore Management University, 2010)
This research aims to understand the psychological motives behind microblogging. We conducted two studies to investigate if social exclusion and existential anxiety would lead to a high tendency to microblog. Our results show that participants did not use microblogging to satisfy their needs for social connection and affiliation, but highly extraverted participants did use it to relieve their existential anxiety.